2009
DOI: 10.1090/s0894-0347-09-00629-8
|View full text |Cite
|
Sign up to set email alerts
|

Singular Kähler-Einstein metrics

Abstract: We study degenerate complex Monge-Ampère equations of the form (ω + dd c ϕ) n = e tϕ µ where ω is a big semi-positive form on a compact Kähler manifold X of dimension n, t ∈ R + , and µ = f ω n is a positive measure with density f ∈ L p (X, ω n ), p > 1. We prove the existence and unicity of bounded ω-plurisubharmonic solutions. We also prove that the solution is continuous under a further technical condition.In case X is projective and ω = ψ * ω ′ , where ψ : X → V is a proper birational morphism to a normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
550
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 331 publications
(564 citation statements)
references
References 44 publications
(22 reference statements)
8
550
0
Order By: Relevance
“…Recently, Shokurov has shown the existence of flips in dimension 4 [34] and Hacon and M c Kernan [8] have shown that assuming the minimal model program in dimension n − 1 (or even better simply finiteness of minimal models in dimension n − 1), then flips exist in dimension n. Thus we get an inductive approach to finite generation.…”
Section: Existence Of Minimal Models For Varieties Of Log General Typmentioning
confidence: 99%
“…Recently, Shokurov has shown the existence of flips in dimension 4 [34] and Hacon and M c Kernan [8] have shown that assuming the minimal model program in dimension n − 1 (or even better simply finiteness of minimal models in dimension n − 1), then flips exist in dimension n. Thus we get an inductive approach to finite generation.…”
Section: Existence Of Minimal Models For Varieties Of Log General Typmentioning
confidence: 99%
“…Kolodziej ([29,30]) proved the existence and Hölder estimate of solution to the complex Monge-Ampère equation when the right hand side is a nonnegative L p function for p > 1. There are further existence and regularity results on the complex Monge-Ampère equation with right hand side less regular or degenerate, see references [3,13,26,4,52,43,27,20,19,22] for details.…”
Section: Introductionmentioning
confidence: 99%
“…The long time existence of the Kähler-Ricci flow on a minimal projective manifold with any initial Kähler metric is established in [TiZha]. The regularity problem of the canonical singular Kähler-Einstein metrics on minimal projective manifolds of general type is intensively studied in [Zh,EyGuZe1].…”
Section: Introductionmentioning
confidence: 99%
“…The unique Kähler-Einstein metric with bounded local potential and the associated Kähler-Einstein measure on the canonical model X can are constructed in [EyGuZe1]. The Kähler-Einstein measure in Theorem C.1 is invariant under birational transformations and so it can be considered as a birational invariant.…”
mentioning
confidence: 99%
See 1 more Smart Citation